The Distant Origins of “Fat Shaming” or why the People of Antiquity did not Ridicule Fat Women - Stachura, Michał (Studia Ceranea, 2022)
The phenomenon of “fat shaming” (in particular with its aspect of the especially harsh criticism of the corpulence in young adult women) seems nearly non-existent in the ancient Classical literature. The extant satirical depictions of fatness are uncommon and aimed, almost exclusively, at overweight men. The author of the paper analyses this satirical description, its background in the ancient moral philosophy, as well as comments on plumpness and gluttony in the context of assessments of the female physical beauty. He also attempts to explain how some ancient ideas may have evolved in the attitudes of today, showing some examples from the 19th-century prose as a step in the reshaping of the ancient ideas. Eventually, the author makes an attempt to offer a better understanding of this contemporary phenomenon, which only in some of its elements may be seen as rooted in Antiquity.